Strategic Planning of Information Systems with Ward and Peppard Method Case Study of Salatiga City Youth and Sports Office - M. Yunus Faizal; Hanna Prillysca Chernovita (Universitas Bina Darma, 2022)
The Salatiga City Youth and Sports Office is a government agency engaged in Youth, Scouting, and Sports. Information systems and information technology (SI / IT) greatly influence the success of an organization in achieving its goals. Currently, the Salatiga City Youth and Sports Office in implementing SI / IT is still not optimal, therefore this research is about the strategic design of information systems using the ward and peppard method. The ward and peppard method consist of SWOT analysis, Value Chain Analysis, PEST Analysis, McFarlan Analysis, and Five Force Model Analysis. The results of this study are recommendations for a portfolio of information systems, namely the Sports Building Lending Information System, the Activity Report Filing Information System, the Athlete Information System, and the Youth Information System. The information system implementation plan will be carried out within the next 4 years.